(untitled) (International journal of artificial intelligence, 2026)
In the contemporary branding landscape, the focus is increasingly shifting beyond products and services toward the deeper philosophical foundations of brands. This article explores how founder identity functions as a central psychological and cultural force in shaping future brands as emotional and cultural ecosystems. Rather than viewing branding solely as a market-driven strategy, the study examines founder-led brands as value-based systems where personal beliefs, life experiences, and emotional narratives of founders are embedded into brand identity. The research highlights how founder psychology influences brand authenticity, consumer trust, and long-term emotional engagement. By analyzing branding evolution through a psychological and cultural lens, this study emphasizes the growing importance of founder brands in creating meaningful, resilient, and future-oriented brand ecosystems that resonate deeply with modern consumers.